The Interaction of Education and the Global Social System: the Experience of China - Serhii Terepyshchyi (Ukrainian Policymaker, 2022)
This paper shows how to change the educator’s role in the modern teaching and learning structure in accordance with the requirements of market relations. The teacher’s position remains rather marginal and archaic. There are four main segments of pedagogical practice in which reforms are needed: 1. Space for pedagogical creativity. 2. Work in the context of the latest advances in technology. 3. Dependence of the teacher’s well-being on the results of his work. 4. Lifelong teacher education. These modern requirements are not fully implemented in any country in the world, but China has an interesting experience worth studying in more detail. Education is now at the crossroads of tradition and innovation, and the final choice is difficult to make, so it is worth looking at the experience. After all, according to the radical scenario, even the «death of the university» as the main centre of higher education is possible.